The Effect of Blockchain Adoption on Fintech Development: The Moderating Role of ‎Organizational Agility, An Empirical Study of Digital Wallet - AL-Magali , Mohannad; Allahham, Mahmoud; Alawneh, Osama Mousa; Ayasrah, Firas Tayseer; Al-Rawashdeh , Ra'ad Nathir Ahmed; Al-Said , Khaleel (International Journal of Basic and Applied Sciences, 2025)
This article investigates the moderating effect of organizational agility on the association between ‎blockchain adoption and fintech development, focusing on the digital wallet in Jordan. Transforming ‎the digital economy with financial technologies, blockchain, a foundational innovation, offers ‎improved transparency, security, and operational efficiency. However, the extent to which these ‎benefits materialize depends on an organization’s ability to respond quickly to change, a quality ‎known as organizational agility. In line with this, we explore how the adoption of blockchain adds to ‎the relationship between fintech development outcomes and how organizational agility interplays in ‎this relationship. We adopted a quantitative methodology that involved employees and stakeholders ‎in the digital wallet. The results show that blockchain adoption positively influences fintech ‎development, and organizational agility significantly moderates this relationship. Such findings ‎provide practical contributions for fintech firms and technology strategists to use blockchain ‎innovations to grow dynamically in organizations, in Jordanian emerging financial markets‎.